2004
DOI: 10.1128/iai.72.11.6206-6210.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofCandida albicansMorphogenesis by Fatty Acid Metabolites

Abstract: Candida albicans is an opportunistic dimorphic fungus that inhabits various host mucosal sites. Conversion from the yeast to the hyphal form has been associated with increased virulence and mucosal invasiveness. C. albicans morphogenesis is regulated by multiple signals and signaling pathways. However, signals that control morphogenesis in vivo are unknown. We investigated the effects of host long chain fatty acids, eicosanoids, and bacterial short chain fatty acids on control of germination. None of the C 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(190 citation statements)
references
References 48 publications
6
178
2
Order By: Relevance
“…One study showed the probiotic bacteria Lactobacillus acidophilus and Lactobacillus casei induce protection against systemic candidiasis in mice (Wagner et al 2000). Shortchain fatty acids (butyric acid) produced by lactic acid bacteria also inhibit filamentation and may prevent C. albicans from causing disease in the gut (Noverr and Huffnagle 2004a).…”
Section: Cross-kingdom Interactionsmentioning
confidence: 99%
“…One study showed the probiotic bacteria Lactobacillus acidophilus and Lactobacillus casei induce protection against systemic candidiasis in mice (Wagner et al 2000). Shortchain fatty acids (butyric acid) produced by lactic acid bacteria also inhibit filamentation and may prevent C. albicans from causing disease in the gut (Noverr and Huffnagle 2004a).…”
Section: Cross-kingdom Interactionsmentioning
confidence: 99%
“…The area occupied by hyphae and yeast cells (in mm) was determined for each image using the ImageJ program (version 1.32 for Windows), a public domain image processing program developed at the National Institutes of Health (NIH), Bethesda, USA. All areas of hyphae and yeast cells in each section were summed and the result was log 10 transformed.…”
Section: G Mellonella Histological Analysismentioning
confidence: 99%
“…All of these strains were able to inhibit the growth of C. albicans, but the inhibitory effects were dependent on the strain tested, dose administered and duration of treatment. [10][11][12] Therefore, further studies are needed to elucidate the inhibitory activity of Lactobacillus strains against C. albicans, particularly in terms of biofilm formation, filamentation capacity and infection potential.…”
Section: Introductionmentioning
confidence: 99%
“…and C. albicans have antagonistic relationship inside the gut. Even if not able to completely eradicate C. albicans, the bacterium could inhibit the growth and virulence of C. albicans by the production of hydrogen peroxide and organic acids [104,105]. Moreover, commensal Lactobacilli produce the metabolite indole-3-aldeyde (IAld) by tryptophan metabolism, activating the Ahr mediated IL-22 response which in turns reduces colonization by C. albicans [43].…”
Section: Fungi Inhabiting the Gutmentioning
confidence: 99%